Five little ducks : an old rhyme - Paparone, Pamela (Oxford : Heinemann : Nourth-South Books, 2005)
When her five little ducks disappear one by one, Mother duck sets out to find them.
1.5
K-3.
K-3
Keywords: Children's poetry; Nursery rhymes; Counting -- Poetry; Ducks -- Poetry; Nursery rhymes; Children's poetry; Counting -- Poetry; Ducks -- Poetry